2015
DOI: 10.1016/j.neo.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Pro-Survival Protein MET with Tivantinib (ARQ 197) Inhibits Growth of Multiple Myeloma Cells

Abstract: The hepatocyte growth factor (HGF)/MNNG HOS transforming gene (MET) pathway regulates cell growth, survival, and migration. MET is mutated or amplified in several malignancies. In myeloma, MET is not mutated, but patients have high plasma concentrations of HGF, high levels of MET expression, and gene copy number, which are associated with poor prognosis and advanced disease. Our previous studies demonstrated that MET is critical for myeloma cell survival and its knockdown induces apoptosis. In our current stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…As shown in Fig. 2f, these changes are linked to the activation of oncogenes involved in multiple myeloma including SYK [43][44][45][46][47] , MET [48][49][50] and SH3GL3 51 in NSD2 overexpressing cells ( Fig. 2f).…”
Section: New Ctcf and H3k27ac Peaks Are Located Within Expanded H3k36mentioning
confidence: 87%
“…As shown in Fig. 2f, these changes are linked to the activation of oncogenes involved in multiple myeloma including SYK [43][44][45][46][47] , MET [48][49][50] and SH3GL3 51 in NSD2 overexpressing cells ( Fig. 2f).…”
Section: New Ctcf and H3k27ac Peaks Are Located Within Expanded H3k36mentioning
confidence: 87%
“…In vivo and in vitro experiments confirmed its ability to impair the growth of various cancers. [317][318][319] Tivantinib has been investigated as an independent drug or combined with sorafenib in phase II and III trials in patients with liver cancer and combined with erlotinib in phase III trials in patients with NSCLC. Data showed that patients with liver cancer with MET overexpression had a better OS than those without MET overexpression in a phase II trial, but the significance was lost in a phase III trial, while the use of tivantinib contributed little to the prognosis of NSCLC.…”
Section: The Hgf/c-met Pathwaymentioning
confidence: 99%
“…ARQ-197 is a selective inhibitor of c-Met activity, and is found to be non-ATP competitive, therefore retaining its effectiveness in cells [ 44 ]. The efficacy of this SMI has been tested on a number of human cancer cell lines, including MM [ 30 , 45 46 ]. ARQ-197 has also been tested in clinical studies on numerous types of tumour including MM [ 47 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…SU11274 inhibited myeloma cell proliferation and migration in vitro [ 25 , 29 ]. ARQ-197 (Tivantinib), a non-ATP-competitive c-Met inhibitor, induced apoptosis by >50% in 12 human myeloma cell lines, including those resistant to standard chemotherapy, and in a murine xenograft model of MM it was shown to reduce a subcutaneous tumour [ 30 ]. To date the effects of ARQ-197 on myeloma induced-bone disease have not been investigated.…”
Section: Introductionmentioning
confidence: 99%